Formation of a State Support Program for Agricultural Producers in Ukraine Considering World Experience - Pronko, Lyudmila; Furman, Irina; Kucher, Anatolii; Gontaruk, Yaroslav (European Journal of Sustainable Development, 2020)
In our paper we researched the state regulation in agriculture of Ukraine, as well as world experience in this field. The distribution of state financing for support of agricultural production is analyzed. We singled out the direction of state support to the agrarian sector of Ukraine. The directions of organizational reforming of households in the market conditions are investigated. The variants of integration of households of the population into more consolidated economic forms are offered. The priority of the development of cooperatives in agriculture has been argued. The positive experience of state support of servicing cooperation is considered on the example of «The Benefits of the Development of Personal Peasant, Farmers, Cooperative Movement in the Village and Advice Service for 2016-2020» of the Vinnytsia Region. The prospects of creation of cooperatives for the provision of oilseeds processing services for the energy needs of agribusinesses and provision of livestock feed with forages are argued. The prospects for realization of the program of development of agricultural servicing cooperatives within the boundaries of Ukraine are outlined. Keywords: agrarian policy, agribusiness development program, agricultural servicing cooperative agriculture, cooperation, food safety, energy security, enterprise-agro producer, integration of farms, state support of agrarian sector